Ce-Ni mixed oxide as efficient catalyst for H-2 production and nanofibrous carbon material from ethanol in the presence of water - Fang, Wenhao; Pirez, Cyril; Capron, Mickael; Paul, Sebastien; Raja, Thirumalaiswamy; Dhepe, Paresh Laxmikant; Dumeignil, Franck; Jalowiecki-Duhamel, Louise (RSC Advances, 2012)
Hydrogen production from ethanol steam reforming (H2O/C2H5OH = 3) was studied over Ce-Ni based catalysts issued from different preparation methods (co-precipitation (CP), impregnation (IMP) and incipient wetness impregnation (IWI)). Catalysts prepared by the CP method exhibit higher activity and much better stability compared to the other two types of catalysts. The Ni1CeOY-CP catalyst is able to completely convert ethanol at 450 degrees C to H-2, CO2 and CH4 (almost no CO is observed), with a H-2 yield of 3 moles of hydrogen produced per mole of ethanol converted. A very high H-2 yield of 4.6 mol mol(EtOH)(-1) is achieved over the Ni1CeOY-CP mixed oxide at 650 degrees C. Correlations between the preparation method, catalytic activity and stability, and type of carbon deposition are discussed. The CP method forms very active small sized NiO (15 nm) and CeO2 (4 nm) nanoparticles, leading to the formation of a lower amount of carbon deposition in the form of nanofibrous carbon materials, the size of which depends on the Ni related nanoparticles. For CP catalysts, the graphitic filaments obtained correspond to carbon nanofibers (CNFs) and carbon nanotubes (CNTs) with a much smaller and homogenous size compared to the filamentous carbon formed over the catalysts issued from the other preparation methods, in relation to the active particles size. The catalytic stability is attributed to the type of carbon formed.